2000
DOI: 10.1136/heart.84.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve is supranormal in endurance athletes: an adenosine transthoracic echocardiographic study

Abstract: Objective-To compare coronary flow reserve in endurance athletes and healthy sedentary controls, using adenosine transthoracic echocardiography. Methods-29 male endurance athletes (mean (SD) age 27.3 (6.6) years, body mass index (BMI) 22.1 (1.9) kg/m 2 ) and 23 male controls (age 27.2 (6.1) years, BMI 23.9 (2.6) kg/m 2 ) with no coronary risk factors underwent transthoracic echocardiographic assessment of distal left anterior descending coronary artery (LAD) diameter and flow, both at rest and during intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 73 publications
5
35
1
Order By: Relevance
“…At a difference with FFR, CFR has a large inter-individual variability, influenced by age, sex, and physical training among other factors. 31,32 IMR measurements suggest that MCD was absent in group A vessels, supporting previous observations based on Doppler-derived microcirculatory resistance in the same FFR/CFR classification quadrant. 25 Because normal CFR values in group A vessels suggests adequate myocardial blood supply, the benefit of revascularization of epicardial stenoses, despite abnormal FFR, might be challenged.…”
Section: Classification Disagreement Between Ffr and Cfrsupporting
confidence: 75%
“…At a difference with FFR, CFR has a large inter-individual variability, influenced by age, sex, and physical training among other factors. 31,32 IMR measurements suggest that MCD was absent in group A vessels, supporting previous observations based on Doppler-derived microcirculatory resistance in the same FFR/CFR classification quadrant. 25 Because normal CFR values in group A vessels suggests adequate myocardial blood supply, the benefit of revascularization of epicardial stenoses, despite abnormal FFR, might be challenged.…”
Section: Classification Disagreement Between Ffr and Cfrsupporting
confidence: 75%
“…In these situations, a proportional growth would occur between the coronary microvasculature and myocyte hypertrophy. Additionally, in humans, a result similar to that of the present study was observed in athletes with left ventricular hypertrophy 36 . These data suggest that the specificity of the inducing stimulus is important to the development of cardiac hypertrophy, and some of them are also able to induce a physiologic adaptation of the coronary microvasculature.…”
Section: Discussionsupporting
confidence: 92%
“…This differs significantly from observations made previously in patients with acquired hypertrophy due to hypertensive or valvular heart disease (1,9,18,48), in which basal perfusion measurements were normal and hyperemic myocardial perfusion and perfusion reserves were decreased relative to controls. Our observations regarding hyperemic perfusion in the CCHD patients more closely parallel those made in those with the hypertrophy of the "athlete's" heart, in which hyperemic perfusion and perfusion reserves are preserved (21,26). These observations suggest that there may be significant differences in the pathogenesis and pathophysiology of the increase in ventricular mass between CCHD patients and those with acquired forms of ventricular hypertrophy (hypertensive or valvular heart disease).…”
Section: Discussionsupporting
confidence: 66%